2014
DOI: 10.1016/j.pan.2014.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Role of pancreatic fat in the outcomes of pancreatitis

Abstract: The role of obesity in relation to various disease processes is being increasingly studied, with reports over the last several years increasingly mentioning its association with worse outcomes in acute disease. Obesity has also gained recognition as a risk factor for severe acute pancreatitis (SAP) [1–8]. The mortality in SAP may be as high as 30% and is usually attributable to multi system organ failure (MSOF) earlier in the disease, and complications of necrotizing pancreatitis later [9–11]. To date there is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(65 citation statements)
references
References 109 publications
0
54
0
11
Order By: Relevance
“…Adiposity itself increases triglyceride and local and systemic inflammation, which is involved in the development of AP. Complex factors, such as higher secretion of inflammatory mediators, lipotoxicity and necrosis of peripancreatic fat, diabetes/insulin resistance, elevated systemic inflammatory response, and low levels of anti‐inflammatory cytokines, have been implicated as pathogenic mechanisms associated with obesity in AP development . Further, elevated BMI increased the risk of symptomatic cholelithiasis, thereby increasing the risk of gallstone‐related AP.…”
Section: Discussionmentioning
confidence: 99%
“…Adiposity itself increases triglyceride and local and systemic inflammation, which is involved in the development of AP. Complex factors, such as higher secretion of inflammatory mediators, lipotoxicity and necrosis of peripancreatic fat, diabetes/insulin resistance, elevated systemic inflammatory response, and low levels of anti‐inflammatory cytokines, have been implicated as pathogenic mechanisms associated with obesity in AP development . Further, elevated BMI increased the risk of symptomatic cholelithiasis, thereby increasing the risk of gallstone‐related AP.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis is often characterised by elevated serum amylase and lipase levels; however, according to Sepe et al ,18 there was no association between fatty pancreas and serum amylase and lipase concentrations. Recent studies identified obesity as a risk factor for severe acute pancreatitis associated with multisystem organ failure with a mortality rate of up to 30% 31. The implications of pancreatic fat with reference to its proximity to pancreatic acinar cells and the toxic effect on islets have been described 31.…”
Section: Nafpd and Pancreatitismentioning
confidence: 99%
“…Recent studies identified obesity as a risk factor for severe acute pancreatitis associated with multisystem organ failure with a mortality rate of up to 30% 31. The implications of pancreatic fat with reference to its proximity to pancreatic acinar cells and the toxic effect on islets have been described 31. Pancreatic steatosis with superimposed acute pancreatitis has been proven to intensify the inflammation, thereby having a direct toxic effect on pancreas parenchyma; in fact, fat infiltrates adjacent to acinar cells have been associated with more severe parenchymal damage in acute pancreatitis 34 35.…”
Section: Nafpd and Pancreatitismentioning
confidence: 99%
“…The visceral adipose tissue (VAT) was identified as critical source of bioactive proteins—so-called adipokines—during inflammatory diseases [1, 2]. By directly regulating hyperglycemia, glucose intolerance, and insulin resistance, adipokines function as prognostic indicators in several diseases [3, 4].…”
Section: Introductionmentioning
confidence: 99%